Determinants of Career Choice among Students of Institute of Chartered Accountants (Ghana) - Tetteh Zotorvie, Justice Stephen (European Scientific Journal, ESJ, 2016)
The main purpose of this study was to investigate the major factors that influence the career choice among the professional level students of the Institute of Chartered Accountants (Ghana). The study also examined the stage or time in the academic life of the students that they decided on accounting as a career. A questionnaire-based survey was the main method used for this study. Exploratory factor analysis and descriptive analysis were employed to determine the key factors influencing the students’ career choice in accounting and the timing of the students’ decision to choose accounting as a career. The study showed that personal and job prospects factors such as students’ interest in accounting, high earnings expectation, availability of jobs, prestige and teacher influence were the most important factors that influence the career choice among students of The Institute of Chartered Accountants (Ghana). Less important factors included influences of advertisement, peers and parents or family members. The study also revealed that majority of the students, 50.2%, made their decision to pursue a career in accounting at the Senior High School level, followed by 18.6% deciding when they were at Basic School level.